Peranan Analisis Elemen Logo Dan Visual Identitas Dalam Pembangunan Brand: Studi Kasus Aksara Buana - Muhammad Anindya Suryo Adiningrat (Penerbit dan Percetakan, CV. Picmotiv, 2024)
A logo is part of the visual identity which is a marker of the company's brand. We know that people in the past have used logos as a means of worship and prayer. Apart from that, logos are also used as symbols of the family and then used in companies for their brands and marks. The design of a logo intersects with visual identity because without visual identity, the logo and company profile cannot be created according to the client's wishes. This research aims to analyze the logo elements used in the Aksara Buana logo, apart from the importance of consistency and harmony, where creating a brand requires visuals that the audience can remember. The main problem is how to align, shape and design principles of the buana script logo. The results found in this research are that modern design prioritizes simplicity and flexibility in use on various platforms. It is hoped that the achievements of this research will be able to contribute to the development of logo design, especially in the realm of Visual Communication Design.